2012
DOI: 10.4187/respcare.01301
|View full text |Cite
|
Sign up to set email alerts
|

Potential Effects of Corticosteroids on Physiological Dead-Space Fraction in Acute Respiratory Distress Syndrome

Abstract: BACKGROUND: Increased dead-space fraction is common in patients with persistent acute respiratory distress syndrome (ARDS). We evaluated the changes in the oxygenation and dead-space fraction in patients with persistent ARDS after corticosteroid therapy. METHODS: This was a non-randomized non-placebo, controlled observational study including 19 patients with persistent ARDS treated with corticosteroids. We measured P aO 2 /F IO 2 and dead-space fraction at days 0, 4, and 7 after corticosteroids treatment (meth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
12
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 27 publications
0
12
0
Order By: Relevance
“…These reports show the relationship between coagulation activation and respiratory dead space. As mentioned above, the interplay between inflammation and hemostasis has been well described, and on this basis, in ARDS patients treated with corticosteroids, a reduction in respiratory dead space has been reported [ 30 ]. Therefore, our finding of an association between increased respiratory dead space and D-dimer supports the hypothesis that vascular pulmonary disease is a relevant issue in critically ill COVID-19 patients.…”
Section: Discussionmentioning
confidence: 99%
“…These reports show the relationship between coagulation activation and respiratory dead space. As mentioned above, the interplay between inflammation and hemostasis has been well described, and on this basis, in ARDS patients treated with corticosteroids, a reduction in respiratory dead space has been reported [ 30 ]. Therefore, our finding of an association between increased respiratory dead space and D-dimer supports the hypothesis that vascular pulmonary disease is a relevant issue in critically ill COVID-19 patients.…”
Section: Discussionmentioning
confidence: 99%
“…So, corticosteroids in high doses for a short period are proposed in the early phase of ARDS for quick resolution and to prevent progression to lung fibrosis. Methylprednisolone administered to patients with intermediate and late ARDS is associated with improved oxygenation and reduced dead space to tidal volume ratio as early as four days following initiation [13]. In a prospective, randomized trial of methylprednisolone therapy which included 99 patients the investigators concluded that the outcome was not affected in patients with ARDS receiving highdose methylprednisolone [14].…”
Section: Discussionmentioning
confidence: 99%
“…If the balance between these two opposite phenomena favors an overall decrease of ventilation/perfusion ratio, the CO 2 clearance increases and therefore the P a CO 2 decreases. This has been associated to greater survival [24,25]. In contrast, if poor alveolar recruitment occurs (i.e., the dorsal recruited pulmonary units are fewer than the ventral collapsed ones), the upright diversion of the ventilation may lead to an increase of the dead space fraction.…”
Section: Co 2 Clearancementioning
confidence: 99%